Identity and functional characterisation of the transporter supporting the Na+-dependent high-affinity NO3− uptake in Zostera marina L. - Rubio-Valverde, Lourdes; Díaz-García, Jordi; Martín-Pizarro, Carmen; Siverio, José M.; Raven, John A.; Fernández-García, José Antonio (Wiley, 2023)
Zostera marina is a seagrass, a group of angiosperms that evolved from land to live submerged in seawater, an environment of high salinity, alkaline pH and usually very low NO3−. In 2000, we reported the first physiological evidence for the Na+-dependent high-affinity NO3− uptake in this plant. Now, to determine the molecular identity of this process, we searched for NO3− transporters common to other vascular plants encoded in Z. marina's genome. We cloned two candidates, ZosmaNPF6.3 and ZosmaNRT2 with its partner protein ZosmaNAR2. ZosmaNAR2 expression levels increase up to 4.5-fold in Z. marina leaves under NO3−-deficiency, while ZosmaNRT2 and ZosmaNPF6.3 expressions were low and unaffected by NO3−. NO3− transport capacity, kinetic properties and H+ or Na+-dependence were examined by heterologous expression in the Hansenula polymorpha high-affinity NO3− transporter gene disrupted strain (∆ynt1). ZosmaNPF6.3 functions as a H+-dependent NO3− transporter, without functionality at alkaline pH and apparent dual kinetics (KM = 11.1 µM at NO3− concentrations below 50 µM). ZosmaNRT2 transports NO3− in a H+-independent but Na+-dependent manner (KM = 1 mM Na+), with low NO3− affinity (KM = 30 µM). When ZosmaNRT2 and ZosmaNAR2 are co-expressed, a Na+-dependent high-affinity NO3− transport occurs (KM = 5.7 µM NO3−), mimicking the in vivo value. These results are discussed in the physiological context, providing evidence that ZosmaNRT2 is a Na+-dependent high-affinity NO3− transporter, the first of its kind to be functionally characterised in a vascular plant, that requires ZosmaNAR2 to achieve the necessary high-affinity for nitrate uptake from seawater.
Keywords: Zostera marina; Flora marina; Angiospermas; Nitratos; Biología molecular vegetal; Na+‐dependent NO3−transport; NAR2; NPF6.3; NRT2; Seagrasses